Economic and theological approaches to debt cancellation - Robbie Mochrie (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2003)
Differences in economic and theological approaches to debt cancellation result from differences in disciplinary assumptions in respect of purpose, method, and argument. We argue that they provide alternative commentaries upon the need for debt cancellation, but that it is not possible to demonstrate the superiority of one over the other, so practitioners in one are likely to continue to find it difficult to respond meaningfully to arguments from the other.
Keywords: O19; F34; F35; 330; debt cancellation; conditionality; theology